The Politics of the Nazi Past in Germany and Austria, David Art (Cambridge: Cambridge University Press, 2006) 232 pp., cloth 69.00, pbk. 24.99, Adobe e-book 20.00 - Baranowski, Shelley (Holocaust and genocide studies, 2008)
David Art's comparative study focuses on the manner in which the Nazi past has influenced political debate among opinion-makers in Germany and Austria from the end of World War II to the present. Having conducted some two hundred “unstructured” interviews with politicians, public intellectuals, civic activists, and journalists in both countries, and having researched an extensive survey of periodicals, Art argues that debates among elites have been primarily responsible for influencing the public's position toward Nazism. In Germany elites have forged a “culture of contrition,” a consensus that marginalizes right radicalism, accepts Germany's responsibility for the Second World War, and recognizes the Holocaust as the defining event of German history.